Biodiesel Production through Catalytic Microwave In-situ Transesterification of Micro-algae (Chlorella sp.) - Mahfud, Mahfud; Kalsum, Ummu; Ashwie, Viqhi (International Journal of Renewable Energy Development, 2020)
Aim of this research are to study and develop research related to the potential of Chlorella sp. into biodiesel with the help of microwaves in-situ transesterification by characterizing parameters such as microwave power (300; 450; 600 W) and reaction time (10; 30; 50 minutes) with catalyst concentration of KOH and molar ratio of microalga : methanol are 2% and 1:12 respectively and optimized by response surface methodology with Face Centered Central Composite Design (FCCCD). The study was carried out by dissolving the catalyst into methanol according to the variable which was then put into a reactor containing microalgae powder in the microwave and turned on according to the predetermined variable. After the reaction process is complete, the mixture is filtered and resuspended with methanol for 10 minutes to remove the remaining FAME and then the obtained filtrate is cooled. Water is added to the filtrate solution to facilitate the separation of hydrophilic components before being separated and pushed apart until 3 layers are formed. Amount of FAMEs in the first layer formed were extracted with n-hexane solution and washed with water and the FAME product obtained was then distilled to remove the remaining n hexane and then weighed. The results indicated that yield increased with increasing reaction time and microwave power with the best conditions of 50 minutes each and 440.53 watts with the highest yield reaching 35.72% (dry basis) through using of KOH catalysts with low concentrations, 2%.Â©2020. CBIORE-IJRED. All rights reserved